2010
DOI: 10.1249/mss.0b013e3181d322c4
|View full text |Cite
|
Sign up to set email alerts
|

Fatness, Fitness, and Cardiometabolic Risk Factors among Sixth-Grade Youth

Abstract: Purpose Examine whether cardiometabolic risk factors are predicted by fitness or fatness among adolescents. Methods Participants are 4955 (2614 female) sixth-grade students with complete data from 42 US middle schools. Fasting blood samples were analyzed for total cholesterol, HDL- and LDL-cholesterol, triglyceride, glucose, and insulin concentrations. Waist circumference and blood pressure were assessed. Body mass index (BMI) was categorized as normal weight, overweight, or obese as a measure of fatness. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
11
36
0
1
Order By: Relevance
“…CRF levels have proven to be an independent predictor for MetS in children and adolescents (8,(13)(14)(15). Consistent with previous studies, our data showed that as CRF levels increased, the metabolic risk profile improved (10,14), but when the influence of BMI was controlled, the association between CRF and cardiometabolic risk factors disappeared or was mitigated (13,15).…”
Section: Crf and Metssupporting
confidence: 91%
See 1 more Smart Citation
“…CRF levels have proven to be an independent predictor for MetS in children and adolescents (8,(13)(14)(15). Consistent with previous studies, our data showed that as CRF levels increased, the metabolic risk profile improved (10,14), but when the influence of BMI was controlled, the association between CRF and cardiometabolic risk factors disappeared or was mitigated (13,15).…”
Section: Crf and Metssupporting
confidence: 91%
“…In most of the studies reported to date, CRF appears to be independently associated with cardiometabolic risk even after adjusting for adiposity, although the magnitude of the association appears to be small to moderate when adiposity is included in the models (9,15). Likewise, CRF levels do not completely account for the association between BMI and cardiometabolic risk (15,16).…”
mentioning
confidence: 95%
“…Similar results were reported elsewhere 9,14 suggesting that excess weight during adolescence may be associated with undesirable total cholesterol levels. On the other hand, other studies have not found an association between BMI and cholesterol in adolescents 15,25 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar variations have been found in other countries 10,11 . Many factors have been associated with dyslipidemia in adolescents, such as socio-environmental conditions, behavior patterns, genes, low birth weight, and excess weight 8,[12][13][14][15][16] . Nevertheless, only a few studies explore the relationship between serum lipids and anthropometric and lifestyle variables, considered important confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…One in three children in the United States is overweight or obese and at-risk for metabolic or cardiac disease [1,2]. Modifiable lifestyle risk factors such as physical activity and diet are common targets of intervention [3][4][5].…”
Section: Introductionmentioning
confidence: 99%